THE INFLUENCE OF SELF-EFFICACY AND MOTIVATION IN ENTERING THE WORLD OF WORK ON STUDENTS' WORK READINESS IN THE FACULTY OF ECONOMICS, JAKARTA STATE UNIVERSITY - Hariyati, Siti; Wolor, Christian Wiradendi; Rachmadania, Rizki Firdausi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of self-efficacy and motivation to enter the world of work on student work readiness of the faculty of economics, State University of Jakarta. The method used is a survey method. The respondetnt selection technique uses Propotional Random Sampling which refers to Isaac and Michael’s table so that an affordable population of 441 students is obtaines with a sample of 195 students. The respondents studied in this study were students of the Faculty of Economics, State University of Jakarta, batch 2018. Data were collected through a questionnaire with a likert scale. Based on the results of the research conducted, it was found that Self-Efficacy has a positive and significant effect on Job Readiness. Motivation to Enter the World of Work has a positive and significant effect on Work Readiness. In accordance with the research hypothesis.